Bibliometric analysis of the Ceylon Journal of Historical and Social Studies - Navaneethakrishnan, S.; Weerasinghe, T. S. K. Peiris (Royal Asiatic Society of Sri Lanka, 2014)
Library and Information Professionals are the informers of the strengths and weaknesses of the research content of a nation. In this context this study especially focuses only on the bibliometric characteristics of articles published in an ancient journal namely “The Ceylon Journal of Historical and Social Studies” published twice a year by the The Ceylon Historical and Social Studies Publication Board which was constituted in 1958. A total of 200 records of articles published in eighteen volumes including volume 1 (1) to V10 (1 & 2) (1958-67)and new series volume 1(1) to V 8 (1) (1971–78) of The Ceylon Journal of Historical and Social Studies and authored by 110 authors during the period 1958-1978(inclusive) were analyzed in this study. There were published during the study period. The objective of this study is to study bibliometric characteristics of “The Ceylon Journal of Historical and Social Studies”. Using Bibliometric analytical method, this study investigates on the distribution output of the publications, authorship pattern, and degree of collaboration. Further this study identifies most productive authors, subject areas, affiliated institutions, and departments of this journal. Findings of the analysis revealed that distributions of publications varyed over the period of study. Highest number of output (17) was recorded in 1958 and 1974. Research growth of publications is increased with positive indicators. Majority of the contributions are single authored (192). Author productivity varied between the observed percentage and expected percentage of authors as predicted by applying Lotka‟s equation. Among the productive authors K.M. De Silva is in the top position with 16 contributions. In the ranked list of affiliated Institutions, University of Ceylon leads others. Departments of History, Economics, and Geography, were identified as top contributing departments. More than 50% of articles have pagination length between 1to 20. Zipf’s law is proportionally not matching with the Frequency list of selected title words of this study. (310 words)
Keywords: Library Science; Bibliometrics; History; Scholarly Communication; Sri Lanka